Investigation of the enhanced photoactivity of CdS/Bi2MoO6/MoSe2 and its application in antibody-free enzyme-assisted photoelectrochemical strategy for detection of N6-methyladenosine and FTO protein. (December 2022) - Cui, X.; Zhou, Y.; Zheng, Y.; Cao, L.; Gao, L.; Duan, J.; Yin, H.; Ai, S.
Abstract: N 6 -methyladenosine (m 6 A) is the most abundant and dynamic reversible modification of mRNA in eukaryotes discovered in the mid-1970s, which is widely involved in various physiological processes. Fat mass and obesity-associated protein (FTO protein) is not only a demethylase for m 6 A, but also a carcinogenic factor for many human cancers. Therefore, it is very important to build a simple and sensitive platform for simultaneous detection of m 6 A and FTO protein. To achieve this aim, a novel photoelectrochemical biosensor was constructed with the antibody-free detection strategy of DTT mediated –SH functionalization of m 6 A triggered by FTO protein catalyzed m 6 A oxidation. To achieve high detection sensitivity, CdS/Bi2 MoO6 /MoSe2 system with matched energy gap was employed as photoactive material. To achieve high detection selectivity, the –CH3 of m 6 A in the captured RNA sequence (m 6 A RNA) on the electrode surface was oxidized by FTO protein to form hydroxymethyl, followed with the covalent reaction of DTT with hydroxymethyl, making the labeling of m 6 A with –SH. Finally, a CdS nanoparticle was modified on the electrode through the specific covalent reaction between –SH and Cd, achieving the improvement of the photocurrent with the matched energy band. Under the optimal experimental conditions, the biosensor showed linear range from 0.001 to 50 nM and 0.0005–500 μg/L with the detection limit of 0.37 pM and 0.034 ng/L (S/N = 3) for m 6 A RNA and FTO protein, respectively. The applicability of the developed method was assessed by investigating the effect of entacapone on FTO protein activity. Graphical abstract: Image 1 Highlights: Enhanced photoactivity of CdS/Bi2 MoO6 /MoSe2 was achieved. An antibody-free PEC biosensor for detecting m 6 A and FTO was constructed. m 6 A was recognized by the oxidation of its –CH3 by FTO. The detection limits were 0.37 pM for m 6 A RNA and 0.034 ng/L for FTO. The effect of antibiotics on FTO oxidation activity was investigated.